Fattah, Irfan Abdul Hamid. “The General Conceptual Framework of the Epistemological Theory in the Qur’an,” Year 4, Issue 15 (Winter 1419 AH/ 1999 CE), Pp. 73-88. - فتاح, عرفان عبد الحميد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1999)
Irfan Fattah’s study sets a theoretical epistemological framework that directs any research in epistemological theory through the Qur’an, emphasizing that it is not separate from the holistic worldview on existence and life. It details the impact of religion in the collective consciousness of the Ummah and in human and social life. It addresses the theory of the “centrality of the individual human being” (which has referred life to absurdity amidst the absence of divine revelation) and the attempt to transform the Qur’an’s supremacy into practical programs capable of activating the Qur’anic discourse. It also specifies the characteristics of the Islamic epistemological theory such as professing the supremacy of the Qur’an, differentiating between the realms of the unseen (ʿālam al-ghayb) and the realm of the evident (ʿālam al-shahādah), and professing the centrality of the Creator and recognition of moderation in the formulation of the epistemological theory.